Synthesis and reactions of β-diketiminate-supported complexes with Mg-Fe or Yb-Fe bonds. - Blake, M; Kaltsoyannis, N; Mountford, P (2013)
Reaction of [M(NacNac)I(THF)]n (M = Mg, Ca or Yb; n = 1 or 2) with KFp gave Mg(NacNac)Fp(THF) (, Mg-Fe = 2.6326(4) Å) or [M(NacNac)(μ-Fp)(THF)]2 (M = Ca or Yb (10), no M-Fe bonds); reaction of with [YbFp2(THF)3]2 gave [{Yb(NacNac)(THF)}2(μ-YbFp4)] (Yb-Fe = 2.9758(5)-3.1702(5) Å) containing the first example of a lanthanide bound solely to four transition metals; reaction of with TolNCNTol gave Mg(NacNac){(NTol)2CFp} via the first net insertion of an unsaturated substrate into an alkaline earth-transition metal bond (NacNac = HC{C(Me)N(2,6-C6H3(i)Pr2)}2; Fp = CpFe(CO)2; Tol = 4-C6H4Me).